Energy values of solvent-extracted canola meal and expeller-derived canola meal for broiler chickens and growing pigs determined using the regression method - Zhong, Ruqing (J Anim Sci, 2019)
The energy values of solvent-extracted canola meal (SECM) and expeller-derived canola meal (EDCM) for broiler chickens and growing pigs were determined in 2 experiments using the regression method. Corn–soybean meal reference diet (RF) and 4 test diets were prepared. The test diets consisted of SECM or EDCM that partly replaced the energy sources in the RF at 100 or 200 g/kg, respectively. The ratios of all energy ingredients were kept similar across all experimental diets. In Exp. 1, a total of 300 birds were fed standard broiler starter diet from days 0 to 19 posthatching. On day 19, 240 birds (776 ± 79.3 g initial BW) were assigned into 5 experimental diets in a randomized complex block design with BW as a blocking factor. Excreta were collected from days 23 to 25 and ileal digesta were collected after birds were euthanized by CO(2) asphyxiation on day 26. In Exp. 2, 40 barrows (28.4 ± 1.6 kg initial BW) were allotted to 5 experimental diets according to the randomized complete block design with BW as a blocking factor. After 5-d adaption period, the feces and urine samples were collected for 5 d by total collection method. The ileal digestible energy (IDE), apparent ME (AME), and nitrogen-corrected apparent ME (AME(n)) in Exp. 1 and the DE, AME, and AME(n) in Exp. 2 for experimental diets and canola meals were determined. In Exp. 1, the inclusion of canola meals to RF linearly decreased the IDE, AME, and AME(n) for birds fed SECM diets (P < 0.01) and the AME and AME(n) for birds fed EDCM diets (P < 0.01). Furthermore, quadratic effects were also found in the IDE, AME, and AME(n) by the inclusion of EDCM to RF (P < 0.05). The IDE were 2,194 and 3,514 kcal/kg DM for SECM and EDCM in broiler chickens, respectively. The respective ME and ME(n) values were 1,919 and 1,695 kcal/kg DM for SECM and 3,134 and 2,937 kcal/kg DM for EDCM. In Exp. 2, the SECM or EDCM addition to RF linearly decreased the AME and AME(n) for pigs (P < 0.01). The DE content was also decreased linearly with the increasing level of SECM (P < 0.01). The DE, ME, and ME(n) of SECM for pigs were 3,109, 2,891, and 2,655 kcal/kg DM, respectively. The EDCM contained 3,850 kcal of DE, 3,581 kcal of ME, and 3,491 kcal of ME(n)/kg DM for pigs. In conclusion, the energy values of EDCM are greater than those of SECM for broiler chickens and pigs, and pigs utilize more of the GE in SECM and EDCM than broiler chickens.